2007
DOI: 10.1097/01.rlu.0000257180.03964.51
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT Localization of Phosphaturic Mesenchymal Neoplasm Causing Tumor-Induced Osteomalacia

Abstract: Tumor-induced osteomalacia (TIO), also known as oncogenic osteomalacia (OO), is a rare syndrome characterized by muscle and bone pain, osteomalacia, low serum 1,25-dihydroxy vitamin D, hypophosphatemia, and hyperphosphaturia. This syndrome is caused by a phosphaturic hormone-secreting mesenchymal neoplasm, which is usually benign but often occult. Since excision of the tumor is curative, preoperative tumor localization is essential. However, despite the many radiologic and scintigraphic imaging techniques avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…One of the most difficult features of the management of osteogenic osteomalacia can be localizing the offending tumor. The general approach to localization involves functional imaging (combined 18 F-fluorodeoxyglucose–positron-emission tomography and CT 18 or indium-111–labeled pentetreotide 19 or both 20 ), followed by anatomical imaging (CT or MRI or both) of suspicious areas that have been identified on functional imaging, as was done in this case. Selective venous sampling, also performed in this case, may be an important tool in cases in which more certainty is needed.…”
Section: Discussion Of Managementmentioning
confidence: 99%
“…One of the most difficult features of the management of osteogenic osteomalacia can be localizing the offending tumor. The general approach to localization involves functional imaging (combined 18 F-fluorodeoxyglucose–positron-emission tomography and CT 18 or indium-111–labeled pentetreotide 19 or both 20 ), followed by anatomical imaging (CT or MRI or both) of suspicious areas that have been identified on functional imaging, as was done in this case. Selective venous sampling, also performed in this case, may be an important tool in cases in which more certainty is needed.…”
Section: Discussion Of Managementmentioning
confidence: 99%
“…In many cases, CT and MRI are not contributory in diagnosing oncogenic osteomalacia [3] because this tumor is often small, grows slowly, and develops in unpredictable locations such as feet [17], mandibular ramus [18], and frontal bone [19]. Previous case reports suggested that 18 F-FDG PET/CT is a useful modality in detection of oncogenic tumors causing oncogenic osteomalacia [11][12][13][14][15]. In the present report, the mesenchymal tumor causing oncogenic osteomalacia was easily detected by 18 F-FDG PET/CT.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only a few case reports have evaluated the feasibility of 18 F-fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET)/CT in detecting occult mesenchymal tumors in oncogenic osteomalacia [11][12][13][14][15]. Despite the benign nature of mesenchymal tumors, each case report indicated that the mesenchymal tumor associated with oncogenic osteomalacia exhibited relatively high 18 F-FDG uptake and was easily detected by 18 F-FDG PET/CT.…”
Section: Introductionmentioning
confidence: 99%
“…Investigation tools include MRI, [13][14][15][16][17][18][19] octreotide scintigraphy, [20][21][22][23][24][25] 201 TI scintigraphy, 26 99m Tc-MIBI scintigraphy, 26,27 and F-18 FDG positron emission tomography (PET) [28][29][30] (Table). MRI is the investigation of choice owing to its high sensitivity.…”
Section: Discussionmentioning
confidence: 99%